NILAI-NILAI SOSIAL DALAM NOVEL REMEMBER WHEN KARYA WINNA EFENDI: PENDEKATAN SOSIOLOGI SASTRA - Resmania Halawa (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
This novel discusses how to help teenagers resolve conflicts that cause them to be restless. This study shows that the value of social sense in today's teenagers has begun to diminish or begin to disappear. The goal of this study is to talk about the social values in Winna Efendi's novel Remember When. In this study, qualitative research using a descriptive approach was used. According to the findings of this study, the novel Remember When by Winna Efendi contains 12 quotes about three social values. The social values of compassion, responsibility, and life harmony are the social values that dominate the novel Remember When by Winna Efendi. Other social values include: The researcher suggests that: 1) the results of this study can be used as a reference when creating a literary work, including a novel; 2) readers of the novel can use this study as information to review the novel's social values; and 3) additional researchers can use this study as a reference when conducting additional research.